2016
DOI: 10.3109/2000656x.2016.1151435
|View full text |Cite
|
Sign up to set email alerts
|

Breast free flap complications related to haematoma formation – do the risks of multiple antithrombotics outweigh the benefits today?

Abstract: Background Free flap reconstruction is today a common operation for many breast cancer patients, but local protocols for microsurgery still predict the use of antithrombotic agents. Reduced operation times and complication rates together with faster mobilisation, after introduction of perforator flaps, call for less comprehensive antithrombotic regimens. It was hypothesised that multiple antithrombotics was a risk factor for bleeding-related flap complications. Methods A retrospective cohort study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…This was scrutinised by the Trial Steering Committee mid-way through the trial and concluded to be surgery-related. A literature search indicated that the rate of haematoma requiring surgical intervention was in line with other studies and therefore is not likely to be increased by the heating process [14, 21, 22]. No other complications, SAEs, SARs or ARs were attributable to the heating procedure; therefore, we can conclude that this is a safe intervention.…”
Section: Discussionsupporting
confidence: 83%
“…This was scrutinised by the Trial Steering Committee mid-way through the trial and concluded to be surgery-related. A literature search indicated that the rate of haematoma requiring surgical intervention was in line with other studies and therefore is not likely to be increased by the heating process [14, 21, 22]. No other complications, SAEs, SARs or ARs were attributable to the heating procedure; therefore, we can conclude that this is a safe intervention.…”
Section: Discussionsupporting
confidence: 83%
“…Dextran was omitted from the standard treatment at our department in 2011 since there was evolving evidence showing no beneficial effect with dextran used in head and neck free flaps, but rather an increased risk for systemic complications. 13 Over the last decade, most centers have abandoned the use of dextran because several studies have confirmed that it does not decrease the risk for thrombosis and flap failure 7 , 14 16 …”
Section: Discussionmentioning
confidence: 99%
“…The lower rates found in our institutional data are supported by a previous review article outlining URO for hematomas in microvascular free tissue transfers, noting rates ranging from 0.2% to 9%. 44 Halle et al 45 reported a 13% incidence of reoperations for hematomas in breast free flaps, highlighting the potential risk of antithrombotic use and importance of using drains. A study assessing risk factors for hematoma formation in 883 patients who underwent mastectomy and immediate reconstruction found no measurable preoperative, operative, or oncologic risk factors, citing that meticulous hemostasis may be 1 of the factors.…”
Section: Discussionmentioning
confidence: 99%